Sex Differences in Omega‐3 and ‐6 Fatty Acids and Health Status Among Young Adults With Acute Myocardial Infarction: Results From the VIRGO Study. Issue 11 (22 September 0207) - Lu, Yuan; Ding, Qinglan; Xu, Xiao; Spatz, Erica S.; Dreyer, Rachel P.; D'Onofrio, Gail; Caulfield, Michael; Nasir, Khurram; Spertus, John A.; Krumholz, Harlan M.
Abstract : Background: Young women (aged ≤55 years) with acute myocardial infarction (AMI) have poorer health status outcomes than similarly aged men. Low omega‐3 fatty acids (FAs) have been implicated as risk factors for cardiovascular outcomes in AMI patients, but it is not clear whether young women have similar or different post‐AMI omega‐3 FA profiles compared with young men. Methods and Results: We assessed the sex differences in post‐AMI omega‐3 FAs and the associations of these biomarkers with patient‐reported outcomes (symptom, functioning status, and quality of life) at 12‐month follow‐up, using data from 2985 US adults with AMI aged 18 to 55 years enrolled in the VIRGO (Variation in Recovery: Role of Gender on Outcomes of Young Acute Myocardial Infarction Patients) study. Biomarkers including eicosapentaenoic acid, docosahexaenoic acid, arachidonic acid (AA), eicosapentaenoic acid/AA ratio, omega‐3/omega‐6 ratio, and omega‐3 index were measured 1 month after AMI. Overall, the omega‐3 FAs and AA were similar in young men and women with AMI. In both unadjusted and adjusted analysis (controlling for age, sex, race, smoking, hypertension, diabetes mellitus, body mass index, and health status score at 1 month), omega‐3 FAs and AA were not significantly associated with 12‐month health status scores using the Bonferroni corrected statistical threshold. Conclusions: We found no evidence of sex differences in omega‐3 FAs and AA in young men and women 1 month after AMI. Omega‐3 FAs and AA at 1‐month after AMI were generally not associated with 12‐month patient‐reported health status after adjusting for patient demographic, clinical characteristics, and the corresponding 1‐month health status score.